(untitled) (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The paper provides a spirited defense of autoethnography as a legitimate viable anti-colonial methodology for sociolinguistic research, particularly within the normative multilingual contexts that characterizes global south linguistic communities. The author, using the story of his unplanned encounter with a seven-year-old boy, Omphile, illustrates the value of making research sense of what may appear as mundane personal experiences and encounters.